2013
DOI: 10.1002/jhet.968
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tetrazoloquinoline‐Based Mono‐ and Bisphosphonate Esters as Potent Anti‐Inflammatory Agents

Abstract: View this article online at wileyonlinelibrary.com.Several new α-alkoxyand α-hydroxyphosphonate derivatives of tetrazole-quinolines were synthesized from the reaction of 2-azidoquinolines 3-carboxaldehyde 1a,b with trialkyl phosphites and dialkyl phosphites. On the other hand, azaphospholes 12a,b were obtained by treating 1a,b with tris(dimethylamino) phosphine. Furthermore, Perkin-type condensation of 1a,b and tetraethyl methylenebisphosphonate provided the corresponding tetrazoloquinoline-based bisphosphonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Dialkyl phosphonate analogs 187 (R = H) were isolated from the reactions of 186 with (RO) 2 POH (Scheme 82). [182] N-Phthalonyl-alanylazide 188 reacted with excess of (RO) 3 P via Staudingerphosphoraneimine intermediates to afford the phosphonates 189 (Scheme 83). [183] Conversely, treatment of 188 with ( i PrO) 3 P afforded 189c, together with the vinyl phosphate 190 (Scheme 83).…”
Section: Reactions With Diazo-and Azido Compoundsmentioning
confidence: 99%
“…Dialkyl phosphonate analogs 187 (R = H) were isolated from the reactions of 186 with (RO) 2 POH (Scheme 82). [182] N-Phthalonyl-alanylazide 188 reacted with excess of (RO) 3 P via Staudingerphosphoraneimine intermediates to afford the phosphonates 189 (Scheme 83). [183] Conversely, treatment of 188 with ( i PrO) 3 P afforded 189c, together with the vinyl phosphate 190 (Scheme 83).…”
Section: Reactions With Diazo-and Azido Compoundsmentioning
confidence: 99%
“…Based on previous reports [2426] that recognized the pyridazine nucleus is being suitable for anti-inflammatory and antinociceptive agents, and by the fact that ring-fused heterocycles containing more than one nitrogen atom (e.g., tetrazole nuclei [21–23]) are key structures in a large variety of biochemical processes, bioscreening of the synthesized substituted tetrazolo[1,5- b ]pyridazine-phosphor derivatives was carried out. Thus, keeping the tetrazolopyridazine core structure intact, we studied the effect of different phosphorus-containing moieties on their antinociceptive and anti-inflammatory effects.…”
Section: Biological Assaysmentioning
confidence: 99%
“…As a part of our continued interest in the development of convenient synthetic approaches to β-enamino- and α-aminophosphonates with anti-inflammatory properties [1320], we recently successfully synthesized a series of mono- and bisphosphonate-based tetrazolo[1,5- a ]quinolines with marked anti-inflammatory properties [2122]. Following this, synthesis of the target compounds, substituted tetrazolo[1,5- b ]pyridazinphosphor esters, is described herein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoline derivatives exhibit various types of biological effects, including antibacterial, [1][2][3][4] tuberculostatic, [5][6][7] antimalarial, 8 and antitumor activity. 9,10 It was also found that quinoline derivatives containing phosphonate or phosphine oxide fragments 11,12 possess antiinflammatory 13 and antiHIV activity. 14 Besides that, we previously showed that hydrazones of isoniazid and dimephosphone (antacid medication, dimethyl (2-methyl-4-oxopent-2-yl)phosphonate) 15 or its Р,С-analogs, dialkyl (2-methyl-4-oxopentyl)phosphine oxides, 16 are significantly less toxic compared to isoniazid, while maintaining its therapeutic effect.…”
mentioning
confidence: 97%